Multi‐Step Crystallization of Self‐Organized Spiral Eutectics. Issue 8 (23rd January 2020) - Moniri, Saman; Bale, Hrishikesh; Volkenandt, Tobias; Wang, Yeqing; Gao, Jianrong; Lu, Tianxiang; Sun, Kai; Ritchie, Robert O.; Shahani, Ashwin J.
Abstract: A method for the solidification of metallic alloys involving spiral self‐organization is presented as a new strategy for producing large‐area chiral patterns with emergent structural and optical properties, with attention to the underlying mechanism and dynamics. This study reports the discovery of a new growth mode for metastable, two‐phase spiral patterns from a liquid metal. Crystallization proceeds via a non‐classical, two‐step pathway consisting of the initial formation of a polytetrahedral seed crystal, followed by ordering of two solid phases that nucleate heterogeneously on the seed and grow in a strongly coupled fashion. Crystallographic defects within the seed provide a template for spiral self‐organization. These observations demonstrate the ubiquity of defect‐mediated growth in multi‐phase materials and establish a pathway toward bottom‐up synthesis of chiral materials with an inter‐phase spacing comparable to the wavelength of infrared light. Given that liquids often possess polytetrahedral short‐range order, our results are applicable to many systems undergoing multi‐step crystallization. Abstract : Eutectic crystallization involves the growth of solid phases from a liquid. This work investigates the origins of certain eutectics that grow into spiral geometry. The results demonstrate that the spiral formation follows a two‐step process, wherein the first step is mediated by the low solid–liquid interfacial energy of a precursor phase, and the second step by crystallographic defects on the precursor.